Low temperature method for synthesis of MgNb2O6 and its characterization - Dubey, K K; Nayar, V (Recent Research in Science and Technology, 2012)
There are various methods for synthesizing luminescent semi-conductor nano-particles. A sample at chemical root of low temperature method was used to synthesize the magnesium niobate (MgNb2O6) nano-particles by using Niobium pentaoxide (Nb2O5), Magnesium nitrate, Ammonium carbonate were used. All chemicals was taken A.R. Grade (99.99%). Ammonium carbonate and Ammonium hydroxide was used to precipitate magnesium carbonate as Mg2+ cation and Niobium hydroxide as a Nb5+ cations under basic conditions. This precipitate was heating at 800°C it produced MgNb2O6 fine powders. The lattice parameters were studied by least square method and obtained a = 5.687 A°, b = 13.975 A° and C = 4.938 A°. The average particle size of MgNb2O6 were studied by Scaning Electron Microscope (SEM) and found to be 45 nm. The crystallite size calculated from Scherrer's formula.